Understanding Hyaluronan Receptor (CD44) Interaction, HA-CD44 Activated Potential Targets in Cancer Therapeutics - Gul-e-Saba Chaudhry (Tabriz University of Medical Sciences, 2020)
Cancer is a complex mechanism involving a series of cellular events. The glycoproteins such as hyaluronan (HA) are a significant element of extracellular matrix (ECM), involve in the onset of cancer developmental process. The pivotal roles of HA in cancer progression depend on dysregulated expression in various cancer. HA, also gain attention due to consideration as a primary ligand of CD44 receptor. The CD44, complex transmembrane receptor protein, due to alternative splicing in the transcription process, various CD44 isoforms predominantly exist. The overexpression of distinct CD44 isoforms (CD44v) standard (CD44s) depends on the tumour type and stage. The receptor proteins, CD44 engage in a variety of biological processes, including cell growth, apoptosis, migration, and angiogenesis. HA-CD44 interaction trigger survival pathways that result in cell proliferation, invasion ultimately complex metastasis. The interaction and binding of ligand-receptor HA-CD44 regulate the downstream cytoskeleton pathways involve in cell survival or cell death. Thus, targeting HA, CD44 (variant and standard) isoform, and HA-CD44 binding consider as an attractive and useful approach towards cancer therapeutics. The use of various inhibitors of HA, hyaluronidases (HYALs), and utilizing targeted Nano-delivery of anticancer agents and antibodies against CD44, peptides gives promising results in vitro and in vivo. However, they are in clinical trials with favourable and unfavourable outcomes, which reflects the need for various modifications in targeting agents and a better understanding of potential targets in tumour progression pathways.